EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN SOMATIC AUDITORY VISUALIZATION INTELLECTUALLY (SAVI) TERHADAP KEMAMPUAN PEMECHAN MASALAH MATEMATIS SISWA DI SMP NEGERI 8 PADANGSIDIMPUAN - Tiya Mariyadi Siagian (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2019)
This study aims to describe effectiveness of using SAVI learning model on students’ mathematical problem solving ability at the eighth grade students of SMP Negeri 8 Padangsidimpuan. The research was conducted by using experimental method (one group pretest post test design) with 25 students as the sample and they were taken by using cluster random sampling technique from 271 students. Observation and test were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using SAVI learning model was 3.83 (very good category) and (b) the average of students’ mathematical problem solving ability before using SAVI learning model was 43.56 (fair category) and after using SAVI learning model was 81.91(very good category). Furthermore, based on inferential statistic by using N-Gain showed G = 0.81 (high category). It means, SAVI learning model was effective used on students’ mathematical problem solving ability at the eighth grade students of SMP Negeri 8 Padangsidimpuan.